2019
DOI: 10.33314/jnhrc.v0i0.1960
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Disorders in Nepal: Findings from the Pilot Study

Abstract: Background: The global prevalence of mental disorders is high and has an increasing trend. In Nepal, there is dearth in literature on prevalence of mental disorders based on national representative sample. In this study, we aim to present the findings on the prevalence of mental disorders from the pilot study of National Mental Health Survey, Nepal. Methods: A cross-sectional study was conducted among 1647 participants aged 13 years and above in three districts of Nepal: Dhanusha, Bhaktapur and Dolakha each re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 0 publications
3
63
1
Order By: Relevance
“…Nepal's first national mental health survey begun in November 2017 and is expected to end in January 2021 (Jha et al, 2019). With Specialist Psychiatry programs in 11 colleges, and burgeoning institutional journals, psychiatric research in the country appears poised for a great leap forward.…”
Section: Methodsmentioning
confidence: 99%
“…Nepal's first national mental health survey begun in November 2017 and is expected to end in January 2021 (Jha et al, 2019). With Specialist Psychiatry programs in 11 colleges, and burgeoning institutional journals, psychiatric research in the country appears poised for a great leap forward.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies on mental disorders among older people have been conducted in high‐income countries, with similar studies less common in developing countries such as Nepal. Studies suggest higher prevalence of mental disorders among older people compared to younger adults (Jha et al, 2019). A systematic review among older people in Nepal (Thapa, Visentin, Kornhaber, & Cleary, 2018a) reported prevalence of depressive symptoms ranging from 25.5 to 60.6% among community‐dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the current prevalence of any form of mental disorders was 12.9%. Similarly, current major depressive disorder was found among 0.7% adolescents and 3.4% adults [ 16 ]. A nationwide cross-sectional study conducted among representative adult sample in Nepal in 2013 using Hospital Anxiety and Depression Scale (HADS) demonstrated the age- and gender-adjusted point prevalences of anxiety and depression as 16.2% and 4.1% respectively [ 17 ].…”
Section: Introductionmentioning
confidence: 99%